2017
DOI: 10.1002/eqe.2917
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tests of steel plate shear walls using box‐shape vertical boundary elements with or without infill concrete

Abstract: Summary The steel plate shear wall (SPSW) is an effective lateral force resisting system in which unstiffened steel infill plates are connected to the horizontal and vertical boundary elements (VBEs) on all sides of the plates. The boundary elements must be designed to resist the tension field force of the infill panels. When the VBEs are made from a steel box section, the flange of each box VBE connected with the infill panels can be pulled out‐of‐plane by significant panel forces, called pull‐out action. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has been reported that the fiber‐based beam‐column line element can be effectively applied to simulate the cyclic degradation of RC members . In addition, the shell elements are very effective in simulating the in‐plane or OOP force vs deformation characteristics of steel plates . The BRB core high mode buckling has been studied by using solid elements for the steel core .…”
Section: Numerical Modeling Using a Finite Element Analysis Programmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the fiber‐based beam‐column line element can be effectively applied to simulate the cyclic degradation of RC members . In addition, the shell elements are very effective in simulating the in‐plane or OOP force vs deformation characteristics of steel plates . The BRB core high mode buckling has been studied by using solid elements for the steel core .…”
Section: Numerical Modeling Using a Finite Element Analysis Programmentioning
confidence: 99%
“…23 In addition, the shell elements are very effective in simulating the in-plane or OOP force vs deformation characteristics of steel plates. 24 The BRB core high mode buckling has been studied by using solid elements for the steel core. 25,26 In these studies, the effects of frictions developed between the BRB core and the restrainer including steel casing and infill mortar were incorporated.…”
Section: Numerical Modeling Using a Finite Element Analysis Programmentioning
confidence: 99%
“…In the past few decades, the research and engineering applications of steel plate shear wall (SPSW) have been greatly developed in countries all over the world, such as China, Japan, the United States, and Europe. Advantages of the SPSW system include good ductility, superior energy dissipation capacity, and cost‐effectiveness 1–4 . The main components of a typical SPSW consist of the infill steel plate, horizontal boundary elements, and vertical boundary elements.…”
Section: Introductionmentioning
confidence: 99%
“…Since "New Rural Construction" was proposed by Chinese government in 2005, rural construction in China has been enhanced yearly. Historically, limited to certain economic means, most Chinese rural housing areas adopted masonry structures [6] because masonry houses have simplified construction [7] and good heat insulation [8]. However, brittleness and low bearing capacity [9] caused serious damage of rural masonry housing during earthquakes.…”
Section: Introductionmentioning
confidence: 99%